Monucuentos: Educational material to promote the value of historical monuments in pre-school children - López Cabello, Josefina (Base Diseño e Innovación, 2016)
Monucuentos is a project that arises from the current need to enhance the value of the historical monuments of our country, so as to form citizens aware and concerned of their identity, I.E. Their cultural heritage.